2014
DOI: 10.3233/bd-140372
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing breast cancer treatment pathways in Kumasi, Ghana from onset of symptoms to final outcome: Outlook towards cancer control

Abstract: BACKGROUND Cancer rates are increasing in Africa, including Ghana. Breast cancer is the second most common cancer in incidence and mortality in Ghana. OBJECTIVE We outlined both breast cancer patient characteristics and management at the Komfo Anokye Teaching Hospital (KATH), the main cancer management hospital in central Ghana. Moreover, we identified the treatment interventions predictive of patient outcome. METHODS Medical records of 597 breast cancer patients seen in 2008–2011 were abstracted to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 18 publications
(33 reference statements)
0
42
0
Order By: Relevance
“…A study done in Ghana found that being a member of the Islamic religion, seeking treatment at traditional healers, and a lack of awareness of national health insurance coverage for BC treatment were the main factors that affected treatment completion [45]. A hospital-based study from Ghana revealed that patients diagnosed with late-stage cancer who were put on adjuvant therapy with hormone receptor status evaluation were more adherent to the treatment guidelines compared with those that never had the hormone receptor status determined [46]. A population-based survey from Rwanda and Sierra Leone, looking at the prevalence of breast masses and barriers to care, showed that women were not seeking medical care due to the absence of symptoms of the breast masses, financial issues, and trust in traditional healers, as well as an overall distrust towards the medical system [47].…”
Section: Cancer Control In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…A study done in Ghana found that being a member of the Islamic religion, seeking treatment at traditional healers, and a lack of awareness of national health insurance coverage for BC treatment were the main factors that affected treatment completion [45]. A hospital-based study from Ghana revealed that patients diagnosed with late-stage cancer who were put on adjuvant therapy with hormone receptor status evaluation were more adherent to the treatment guidelines compared with those that never had the hormone receptor status determined [46]. A population-based survey from Rwanda and Sierra Leone, looking at the prevalence of breast masses and barriers to care, showed that women were not seeking medical care due to the absence of symptoms of the breast masses, financial issues, and trust in traditional healers, as well as an overall distrust towards the medical system [47].…”
Section: Cancer Control In Africamentioning
confidence: 99%
“…In Ghana, a study showed that 64.1% of patients presented to facilities at a late stage of the disease for diagnosis [46]. There are significant efforts being made to optimize treatment with limited resources; for example, Rwanda established a central BC treatment center [50].…”
Section: Cancer Control In Africamentioning
confidence: 99%
“…Breast cancer is the second most common cancer among African women, after cervical cancer, and is among the top two leading causes of cancer deaths among Ghanaian women [25]. Globocan estimated the annual incidence rate of breast cancer in Ghana as 25.8 cases per 100,000 women and the mortality rate at 15.2 deaths per 100,000 women, but these rates likely reflect underestimates[6, 7]. In Ghana, data on breast cancer cases are slowly becoming more available through better documentation of hospital admissions, suggesting that Ghana has a higher incidence of breast cancer than estimations from global statistical predictions [3].…”
Section: Introductionmentioning
confidence: 99%
“…From the Western literature, it has been established that prompt initiation of treatment and completion of evidence-based effective treatment are essential to ensure optimal survival, especially in more aggressive breast cancer subtypes, which appear to be more prevalent in African and in women of African extraction in the US, thus, understanding barriers to care and treatment completion within the country will be vital in improving access to care, increasing the utilization of diagnostic and treatment facilities, and facilitating early diagnosis and treatment of the increasing number of patients [11]. We characterized the breast cancer patients seen at Komfo Anokye Teaching Hospital (KATH) and recorded their disease management during the period of 2008–2010, and the current study builds upon the preliminary studies that explored reasons for lack of treatment completion for breast cancer [7, 12]. Because of limited information in some medical records about reasons for lack of completion of prescribed treatment in previous studies, the objective of this study was to identify the diverse salient factors specifically related to incomplete treatment of breast cancer among patients diagnosed at KATH through patient interviews.…”
Section: Introductionmentioning
confidence: 99%
“…1 As a result of increased life expectancies, globalization, and life style changes, demographic transition 3 the incidence of breast cancer has been consistently increased globally. [2][3][4] Each year, breast cancer is newly diagnosed in more than 1 million women worldwide and more than 400,000 women die from it. 5,6 The decision to seek help is influenced by perception on the disease.…”
Section: Introductionmentioning
confidence: 99%